2015
DOI: 10.5348/ijhpd-2015-30-oa-5
|View full text |Cite
|
Sign up to set email alerts
|

Biliary ascariasis in the etiology of recurrent pyogenic cholangitis in an endemic area

Abstract: patients had previous documentation of biliary ascariasis. In three patients bile contained ova of Ascaris lumbricoides and stones in 22 patients contained worm, worm fragments or their ova on histological examination. Overall 24 (80%) patients with recurrent pyogenic cholangitis had past or persistent evidence of biliary ascariasis while only one patient with gallstones had worm fragments on histopathology of stones (p < 0.001). conclusion: We conclude that in endemic areas bacterial infection of the bile duc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…81 Hospital-based studies in India have found that Ascaris may be the cause of approximately half of cases with biliary disease, a third of pancreatitis cases, and around 15% of liver abscesses and biliary lithiasis. [82][83][84] Clinicians in endemic areas must have a high suspicion of Ascaris infection, as cases may present as surgical emergencies.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…81 Hospital-based studies in India have found that Ascaris may be the cause of approximately half of cases with biliary disease, a third of pancreatitis cases, and around 15% of liver abscesses and biliary lithiasis. [82][83][84] Clinicians in endemic areas must have a high suspicion of Ascaris infection, as cases may present as surgical emergencies.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…On repeated invasion, worms often cannot come out of the ductal lumen and die. Subsequent to worm death, sludge and stones form within the bile and hepatic ducts and evolves in to clinical entity of recurrent pyogenic cholangitis[ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of stones is thought to result from the action of bacterial beta-glucuronidase on conjugated bilirubin. 1 Although the exact incidence in India is not known, the disease is quite common in Kashmir 2,3 and eastern parts of India.…”
Section: Introductionmentioning
confidence: 99%
“…2,[8][9][10][11][12] The aim of this article was to report the short and long-term outcomes of surgery for RPC from a tertiary center from Eastern India.…”
Section: Introductionmentioning
confidence: 99%